Crafting clusters: an analysis of the craft beer industry in northern Colorado - Esparza, Timothy R. A. (Kansas State University, 2016)
The following report examines the craft beer industry as a major component of the beverage production cluster in Northern Colorado. By using the four locational determinants derived by Porter (1990) as a framework, this study evaluates the role of geography as a key component in an industry’s ability to foster a competitive advantage. Despite his focus on national competitiveness, Porter's diamond model has influenced strategic thinking on a regional scale (Stimson, Stough & Roberts, 2006). In turn, it can help us to understand the interactions that underlie localized cluster dynamics. The cluster conception in economic development literature assumes that each of Porter's components is equally spatially connected. Resources are focused towards building assets in a region defined by analyzing the cluster. However, factors of the craft beer industry in Northern Colorado did not completely adhere to the traditional parameters of regional cluster geography. Personal interviews with key actors involved in the craft beer industry, along with economic data revealed that local factors are not always the driving force behind the development of the craft beer industry. In addition, the data analysis indicates that determinants of cluster success may be significant at various geographic scales. Locational determinants may not operate within the same area as defined by cluster analysis. Thus, this report closes with a recommendation to consider the significance of proximity when looking to increase the competitiveness of a given industry cluster—for the relationship between locational determinants and geography varies between factors.
Keywords: Craft beer; Porters diamond; Economic development; Industry cluster; Regional economics; Geographic proximity